Outlines of Muhammadan Law - Fyzee, Asaf A. A.; Edited and Revised by Tahir Mahmood (New Delhi Oxford University Press, 2009)
This is the fifth edition of a classic work by a scholar, not just of Islamic law, but also of Islamic jurisprudence, Arabic and Persian. The present edition, revised by one of the formost scholars of Islamic law today, brings the reader up-to-date by adding more than 35 years of new statutory and case law within the format and intellectual design of the original book.
Include Bibliography, Glossary and Index
Keywords: Islamic law -- India -- Freedom of religion (Islamic law)